Caryophyllene Oxide Induces Ferritinophagy by Regulating the NCOA4/FTH1/LC3 Pathway in Hepatocellular Carcinoma - Xiu, Zhiru; Zhu, Yilong; Han, Jicheng; Li, Yaru; Yang, Xia; Yang, Guohua; Song, Gaojie; Li, Shanzhi; Li, Yue; Cheng, Cheng; Li, Yiquan; Fang, Jinbo; et al. (Frontiers in Pharmacology, 2022)
Ferritinophagy is associated with tumor occurrence, development, and therapy effects. Ferritinophagy and ferroptosis are regulated by iron metabolism and are closely connected. LC3 protein is a key protein in autophagy. Following the binding of NCOA4 to FTH1, it links to LC3Ⅱ in lysosomes, a symbol of ferritinophagy. A ferritinophagy’s inducer is likely to open new avenues for anticancer medication research and development. In this study, we discovered that caryophyllene oxide has a substantial inhibitory effect on HCCLM3 and HUH7 cells, by regulating the level of cellular oxidative stress, the levels of autophagy and iron metabolism in HCCLM3 and HUH7 cells, leading to a ferritinophagy-related phenomenon. Furthermore, the results of T-AOC, DPPH free radical scavenging rate, and hydroxyl radical inhibition indicated that caryophyllene oxide can inhibit cell antioxidation. The examination of ferritinophagy-related process revealed that caryophyllene oxide promotes the production and accumulation of intracellular reactive oxygen species and lipid peroxidation. NCOA4, FTH1 and LC3Ⅱ were found to be targeted regulators of caryophyllene oxide. Caryophyllene oxide regulated NCOA4, LC3 Ⅱ and FTH1 to promote ferritinophagy. In vivo, we discovered that caryophyllene oxide can lower tumor volume, significantly improve NCOA4 and LC3 protein levels in tumor tissue and raise Fe2+ and MDA levels in serum. The compound can also reduce NRF2, GPX4, HO-1 and FTH1 expression levels. The reduction of the expression levels of NRF2, GPX4, HO-1 and FTH1 by Caryophyllene oxide also inhibited GSH and hydroxyl radical’s inhibitory capacities in serum, promoted iron deposition in tumor tissue resulting in the inhibition of tumor growth. In summary, our study revealed that caryophyllene oxide mostly kills liver cancer cells through ferritinophagy-mediated ferroptosis mechanisms. In conclusion, caryophyllene oxide may be used as a ferritinophagy activator in the field of anti-tumor drug research and development.